Pola Matematika pada Surat Al Ikhlas - Gema Hista Medika (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
Various studies have been conducted to reveal the order / beauty of the composition and style of language and the contents of Alquran, both in terms of language and numbers contained in Alquran. This study aims to find the mathematical design contained in the letter Al Ikhlas. Surah Al Ikhlas was chosen because of a hadith narrated by Imam Bukhari from Abu Sa'id. Someone heard someone else reading Al Ikhlas and he repeated it. When morning came, he told Prophet Muhammad S.A.W. As if the man was not satisfied with one reading. So the Prophet said,